PERAN DINAS PARIWISATA DALAM PENGEMBANGAN SEKTOR PARIWISATA DAN IMPLIKASINYA TERHADAP KETAHANAN EKONOMI WILAYAH - , Wiwik Vitrianingsih ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesian government policies to conduct regional autonomy have given several regions to dig and manage regional potentials. Tourism hopefully provide contribution to enhance society and regional income. Tourism development conduct depends on the organizer whether it is government, non-government or society to manage. Therefore the role of the Tourism, Culture, Youth, and Sport Office of Sragen Regency is very important. The research was conducted at the Tourism, Culture, Youth, and Sport Office (Disparbudpor) of Sragen Regency. The purpose of the research was gaining description on authority and role of the Tourism, Culture, Youth, and Sport Office in developing tourism at Sragen Regency to support Sragen Regencyâs economy resilience. The research method in use was descriptive qualitative. The data was collected with in-depth interview, observation and document evaluation on the Tourism, Culture, Youth, and Sport Office of Sragen Regency archives. The research result showed the roles of Disparbudpor are: promotion, creating corporation with the related institutions (stakeholder), managing tourism destination, developing cultural value to enhance touristsâ visitation and regional income. The tourism object which gives high contribution is Sangiran Museum tourism object. Disparbudporâs obstacles in developing tourism are: a) loe quality and quantity of tourism human resources, b) Lack coordination of related institutions, c) Limited budget, and d) Lack of societyâs participation. Tourism implication on Sragen Regency regional economy resilience was able to enhance society economy at the surrounding tourism object. Tourism contribution in 2012 is Rp. 1,319,470,750 which was 0.01% of total PAD. It showed the Disparbudporâs work with the whole stakeholder Sragen Regency society.